Cancer mortality in Itapúa—A rural province of Paraguay 2003–2012. (February 2016) - Codas, Manuel; Pesch, Beate; Adolphs, Madita; Madrazo, Carolina; Matthias, Cristian; Heinze, Evelyn; Taeger, Dirk; Behrens, Thomas; Chaux, Alcides; Brüning, Thomas
Highlights: Mortality from cancer outweighed mortality from infectious diseases in Itapúa, Paraguay. Cancer mortality, especially in children, was underestimated due to lack of reliable data. The quality and accuracy of the death certification needs to be improved. The high mortality from cervical cancer requires preventive actions. Tobacco control measures are needed for the primary prevention of lung cancer. Abstract: Background: Itapúa is a rural department in Paraguay with a population of about 500, 000 and a high degree of agro-mechanization for the production of soybean and other crops. So far, only basic health care is provided. Here we analyzed the cancer mortality in this region as a first step towards epidemiological data for cancer prevention. Methods: We calculated the age-adjusted mortality rates according to world standard (AMRWs) for the major cancer sites in both males and females between 2003 and 2012, and estimated the differences between the capital and more central districts of Itapúa vs. remote districts. Results: There were about 2000 cancer deaths in the decade studied, with AMRWs for all malignancies of 90.9/100, 000 in males from central vs . 49.1/100, 000 in remote districts and 69.0/100, 000 vs . 45.0/100, 000 in women. Cancer was mentioned in 12.4% of all death certificates and outweighed mortality from certain infectious and parasitic diseases (3.6%). Cause of death was ill-defined in 19.6% of all death certificates, especially in remote regions and among the elderly. The part of cancer located in the uterus (47.8%) or cell type of neoplasm of the lymphatic or hematopoietic system (73.1%) were often not specified. The uterus (mainly the cervix) (C53–C55) was the leading cancer site in women with AMRWs of 17.2/100, 000 in central and 14.0/100, 000 in remote districts, followed by the breast. Lung and prostate were the leading cancer sites among men. The lung cancer mortality rate was 19.3/100, 000 in the central region but 9.5/100, 000 in remote districts. Although children comprised 36% of the population, only 24 death certificates listed cancer as cause of death in this decade. Conclusions: Analysis of cancer mortality in this rural region of Paraguay, which lacks resources for diagnostics and care, revealed an already large number of cases, with higher rates in the central region than in remote districts. Lung and uterus (primarily the cervix) are common cancer sites and indicate the potential for prevention. However, the quality of the vital statistics needs to be improved. The true cancer burden is most likely underestimated, especially in remote regions and children.